2011
DOI: 10.4103/2229-4708.81096
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric simultaneous determination of Tenofovir disoproxil fumarate and Emtricitabine in combined tablet dosage form by ratio derivative, first order derivative and absorbance corrected methods and its application to dissolution study

Abstract: Three simple, economical, precise, and accurate methods are described for the simultaneous determination of Tenofovir disoproxil fumarate (TE) and Emtricitabine (EM) in combined tablet dosage form. The first method is ratio derivative spectra, second is first-order derivative spectrophotometry and third is absorption corrected method. The amplitudes at 271.07 and 302.17 nm in the ratio derivative method, 224.38 and 306.88 nm in the first order derivative method were selected to determine Tenofovir disoproxil f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 14 publications
0
12
0
1
Order By: Relevance
“…For Solid drug dosage form analysis (Lakshmi et al, 2016;Choudhari et al, 2011), 10 tablets were weighed, powdered in a mortar and 200mg of powder Emtricitabine, 25 mg of Rilpivirine and 300 mg of Tenofovir taken into a 50 mL volumetric lask. The whole mixture was dissolved in a suf icient quantity of diluent, and inally, the solution was diluted to 50ml by adding the same diluent up to the mark.…”
Section: Pharmaceutical Formulation Estimationmentioning
confidence: 99%
“…For Solid drug dosage form analysis (Lakshmi et al, 2016;Choudhari et al, 2011), 10 tablets were weighed, powdered in a mortar and 200mg of powder Emtricitabine, 25 mg of Rilpivirine and 300 mg of Tenofovir taken into a 50 mL volumetric lask. The whole mixture was dissolved in a suf icient quantity of diluent, and inally, the solution was diluted to 50ml by adding the same diluent up to the mark.…”
Section: Pharmaceutical Formulation Estimationmentioning
confidence: 99%
“…The performance order of the proposed methods is BCP > BTB > BPB. The results obtained and shown in (Tables 2 and 3) were compared to those obtained by a reference method [14] by means of -test at 95% confidence level. In all cases, the average results obtained by proposed methods and reference method were statistically identical, as the difference between average values had no significance at 95% confidence level.…”
Section: Validation Of the Proposed Methodsmentioning
confidence: 99%
“…The literature survey revealed that only few methods are available for the determination of tenofovir in dosage forms and include liquid chromatography with tandem mass spectrometry [4,5]; HPLC with solid phase extraction [6]; reversed phase HPLC [7,8]; HPLC with spectrophotometric detection [9]; HPTLC [10]; gradient ion-pair LC with fluorescent detector [11]; and HPLC-UV, HPLC-MS [12], and first-order UV derivative spectrophotometry [13,14]. Visible spectrophotometry, because of its simplicity, costeffectiveness, sensitivity, selectivity, fair accuracy, and precision, has remained competitive in pharmaceutical analysis.…”
Section: Tenofovir Disoproxil Fumarate (Tdf) 9-[(r)-2-[[bis[(isopropomentioning
confidence: 99%
“…In last three decades, derivative spectrophotometry has been extensively used in the determination of drugs in multi components having overlapping spectra, which eliminates interference from formulation matrix by using the zero-crossing techniques [1-4]. Ratio-spectra derivative spectrophotometric method is another useful technique for the estimation of drugs in their mixtures [5-8]. …”
Section: Introductionmentioning
confidence: 99%